Application of silica–alumina oxides of different compositions for removal of C.I. Reactive Black 5 dye from wastewaters - Monika Wawrzkiewicz; Małgorzata Wiśniewska; Vladimir M Gun'ko (Adsorption Science & Technology)
In this paper adsorptive removal of hazardous dye C.I. Reactive Black 5 from aqueous solutions was investigated using the mixed silica–alumina oxides including of 4% SiO 2 and 96% Al 2 O 3 as well as 97% SiO 2 and 3% Al 2 O 3 . The kinetic studies revealed that with the increasing initial dye concentration from 10 to 30 mg/l and contact time from 1 to 240 min, the sorption capacities ( q t ) increased and the equilibrium was observed after 240 min. Sorption of C.I. Reactive Black 5 on 4% SiO 2 and 96% Al 2 O 3 and 97% SiO 2 and 3% Al 2 O 3 takes place through the pseudo-second-order mechanism rather than the pseudo-first-order one. The experimental data were fitted using the Langmuir and Freundlich isotherm models. The effect of the auxiliaries such as anionic surfactant (sodium dodecyl sulphate) and sodium chloride on C.I. Reactive Black 5 removal was investigated in the 10 mg/l C.I. Reactive Black 5–0.1–1 g/l sodium dodecyl sulphate or 5–20 g/l NaCl systems. The potentiometric titrations indicated that the presence of C.I. Reactive Black 5 changed the surface charge density of silica–alumina mixed oxides, especially in the case of 4% SiO 2 and 96% Al 2 O 3 system.